MANFAAT EKONOMI AKTIVITAS BONGKAR MUAT KAPAL-KAPAL POLE AND LINE DI TEMPAT TAMBAT PERAHU - Welem Waileruny; Yosep Pariama; Alex S. W. Retraubun (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2022)
Boat mooring in Dusun Pelita Jaya is used as a loading and unloading place for pole and line fishing vessels even with limited facilities. This research aims to identify infrastructure facilities that support the loading and unloading activities of fishery products and analyze the economic benefits of each economic activity caused. Sampling through interviews and obesity and data is analyzed descriptively qualitatively and quantitatively. The results showed that the infrastructure facilities available are not adequate to support the loading and unloading activities of fishery products, namely cakalang and tuna in the form of logs. The economic benefits caused are direct and indirect benefits that are able to absorb 279 workers. The average value of economic benefits from all activities caused amounted to Rp. 56,771,603,687 or the average of each month amounted to Rp. 4,730,966,974. The largest contribution is made by fish collectors amounting to Rp. 23,622,300,000 or Rp1,968,525,000/month.